Infestation Pattern of Lice In Laying Ducks In Village of Kramat District of Bangkalan Region of Bangkalan - Kiki Amalia Rama; Poedji Hastutiek; Oky Setyo Widodo; Endang Suprihati; Agus Sunarso; Soeharsono Soeharsono (Universitas Airlangga, 2017)
The purpose of this research is to identify lice and to know the pattern of infestation of lice that infest laying ducks in Village of Kramat, District of Bangkalan, Region of Bangkalan. Forty samples of laying ducks were taken in Kramat Village and identified in Entomology and Protozoology Laboratory of Parasitology Department of Veterinary Faculty of Airlangga University, the research was conducted from July to September 2017. This study used an explorative observational research design. Lice taken from a sample of laying ducks are fed into an ointment pot containing 70% alcohol to preserve lice and labeled in accordance with the infected duck's limb region. Identification of lice using Permanent mounting method without coloration. The results of identification, the lice that infest laying ducks consists of three types of Anaticola crassicornis 60%, Menacanthus stramineus 25% and Lipeurus caponis 17.5%. The results of infestation pattern, infected body's region is head-neck, wings and back. The wings infested two types of lice were A. crassicornis and L. caponis, head-neck infested M. stramineus and in the infected back region of A. crassicornis.